Barriers to Regular Student Attendance in Sociology Programs at Mid-West University, Nepal - Anand Prasad Subedi; Bed Prakash Dhakal (MASI Mandiri Edukasi, 2025)
Regular attendance is a crucial factor in students' academic success. However, at Mid-West University (MU) in the Humanities and Social Sciences, irregular attendance among students has been observed. The percentage of students who attend more than 80% of the classes held is zero for undergraduates and only 0.5% for graduates. It is very important to disclose the underlying causes of it. There is no prior research exploring attendance barriers in the context of HSS, MU. Similarly, current institutional policies have not adequately addressed the root causes of student absenteeism. Thus, there is both an empirical and policy research gap. The specific objective of the study is to identify the key barriers that prevent students from attending classes regularly in HSS, MU. The research site for the investigation is the Surkhet district, Karnali Province, based on the programs of HSS and MU. This study has employed a descriptive research design. In-depth interviews and a survey (closed-ended) are the data collection tools. The sample size of the survey is determined based on [ ] formula where the margin of error is 0.05, in which the sample size (n) is 63. Barriers to students' regular attendance in the Humanities and Social Sciences at MU include socio-economic, institutional, academic, and personal factors. This study has both policy and pedagogical implications, suggesting new structural changes and teaching and learning approaches that could be introduced.